Al-Ta‘Allum al-Qā’im ‘alā al-Ansyiṭah li-Ta‘Allum al-Lugah al-‘Arabiyyah bi al-Madrasah al-Ibtidāiyyah al-Islāmiyyah - Nandhera, Alfath; Inayah, Inayah (Study Program of Arabic Language Teaching, 2026)
This study aims to describe the implementation of Activity-Based Learning (ABL) in Arabic language instruction on the topic of hobbies and to analyze students’ levels of learning engagement based on four indicators: participation, interest, response, and confidence. This study employs a mixed-methods approach with a concurrent embedded design. The study population consisted of 28 first-grade students at MI Al-Khoiriyyah 02 in Semarang, comprising 12 males and 16 females. Because the population size was relatively small, total sampling was used, meaning the entire population served as the study sample. Qualitative data were obtained through observation and documentation, while quantitative data were collected using a five-point Likert scale questionnaire. Qualitative data were analyzed descriptively regarding the implementation of ABL, while quantitative data were analyzed using descriptive statistics, including scores and percentages across the four indicators. The results of the study indicate that implementing ABL created a more active, interactive, and student-centered learning environment. Students’ learning engagement levels fell into the good-to-very-good categories, with the interest indicator receiving the highest percentage at 91%, followed by participation at 83%, responsiveness at 80%, and confidence at 78%. These findings indicate that ABL is an effective alternative for enhancing students’ engagement in learning while also improving the quality of Arabic language instruction at Madrasah Ibtidaiyah.